The Concept of "Discourse" in Modern Linguistics - Zavkievna, Salimova Dilnoza (International Journal on Integrated Education, 2023)
The article presents information about new concepts in modern linguistics, including the concept of "discourse". In addition, there are also opinions about the research conducted on the concept of "discourse", the opinions of scientists and their works.